EFFECT OF TIME TO SENTINEL-NODE BIOPSY ON THE PROGNOSIS OF CUTANEOUS MELANOMA - Tejera-Vaquerizo, Antonio (Eur J Cancer, 2015)
INSTRODUCTION: In patients with primary cutaneous melanoma, there is generally a delay between excisional biopsy of the primary tumor and sentinel-node biopsy. The objective of this study is to analyze the prognostic implications of this delay. PATIENTS AND METHOD: This was an observational, retrospective, cohort study in four tertiary referral hospitals. A total of 1963 patients were included. The factor of interest was the interval between the date of the excisional biopsy of the primary melanoma and the date of the sentinel-node biopsy (delay time) in the prognosis. The primary outcome was melanoma-specific survival and disease-free survival. RESULTS: A delay time of 40 days or less (HR, 1.7; CI, 1.2 to 2.5) increased Breslow thickness (Breslow ≥2 mm, HR >3.7; CI 1.4 to 10.7), ulceration (HR 1.6; CI, 1.1 to 2.3), sentinel-node metastasis (HR, 2.9; CI, 1.9 to 4.2), and primary melanoma localized in the head or neck were independently associated with worse melanoma-specific survival (all P<0.03). The stratified analysis showed that the effect of delay time was at the expense of the patients with a negative sentinel-node biopsy and without regression. CONCLUSION: Early sentinel-node biopsy is associated with worse survival in patients with cutaneous melanoma.